Reconstruction of a Long-Term, Reach-Scale Sediment Budget Using Lateral Channel Movement Data as a Proxy: A Case Study on the Lowland Section of the Tisza River, Hungary - Tímea Kiss; Marcell Tóth; Gergely T. Török; György Sipos (Hydrology, 2024)
Humans have influenced the sediment transport of rivers on a centurial scale. Our goal was to use the rate of lateral channel processes as a proxy to reconstruct sediment budget (SB) changes of a lowland river (Middle Tisza, Hungary) on a historical scale (1838–2017). The gross sediment budget (GSB) refers to the total area of eroded and accumulated surfaces, and the net sediment budget (NSB) indicates the sediment sink or source characteristics. At the beginning (1838–1890), the artificial cut-offs increased the slope and channel erosion, but the eroded sediment deposited in the oxbows, so the reach acted as a sediment sink (NSB: +0.1–0.8 m2/m/y). Then (1890–1929), a quasi-equilibrium state developed (NSB: −0.2 m2/m/y to +0.4 m2/m/y). Later (1929–1976), the bank protections impeded lateral erosion, so the system became a sediment sink again (NSB: +0.1–0.7 m2/m/y). Finally (1976–2017), the erosional processes accelerated due to dam construction and revetment collapses, and now the river is a sediment source (NSB: −0.03 to −0.08 m2/m/y). This study proved that (1) the actual SB could not be projected in the long term, as it was heavily modified, and (2) lateral channel changes could be used as a proxy to estimate long-term SB.